2020
DOI: 10.1111/ijfs.14543
|View full text |Cite
|
Sign up to set email alerts
|

Potential of bagasse obtained using hydrothermal liquefaction pre‐treatment as a natural emulsifier

Abstract: Summary Bagasse, a by‐product from raw sugar factories, is conventionally burned for energy production. In this study, bagasse extracts from hydrothermal liquefaction (HTL) treatment (160 °C, 1 MPa and 30 min) with a carbohydrate content of 510.3 mg g−1 and 0.5 mg g−1 of total phenols were applied as emulsifiers in oil‐in‐water (O/W) emulsions. Bagasse extracts from HTL (0.5–4 wt%) lowered the interfacial tension between oil–water interphase from 19.8 to 14.0 mN m−1, owing possibly to the surface‐active hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 66 publications
1
18
1
Order By: Relevance
“…S2). However, the cooling time was reduced and the liquefaction yield was also lower than reported previously (Vodo et al ., 2020). In this study, the cooling time was reduced to 30 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…S2). However, the cooling time was reduced and the liquefaction yield was also lower than reported previously (Vodo et al ., 2020). In this study, the cooling time was reduced to 30 min (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from parameters such as temperature, time, pressure, solid to liquid ratio, and sample composition, heating and cooling rates are also important factors in determining the effectiveness of HTL treatment. It was observed that with 0.5 h cooling time achieved, the cooling rate was 4 °C min −1 , 8 times faster than using the fan (Vodo et al ., 2020). The HTL reactor had provision for cooling water circulation that only passed through the top while the temperature of the reactor cell at the bottom would hardly decrease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dynamic light scattering (DLS) technique using Zetasizer Nano ZS (Malvern Panalytical, Worcestershire, United Kingdom) was applied to determine the particle size and droplet charge, as a protocol adapted from Teo et al (2016) 63 . To avoid multiple scattering effects, for both proceedings, the samples were diluted (1:100) before the analyses 66 . For pH and salt concentration effects, samples were diluted with the same level of pH or ionic strength solution 40 .…”
Section: Methodsmentioning
confidence: 99%